SYARI'AH COMPLIANCE FOR DEVELOPING INNOVATION OF SHARIA BANKING PRODUCTS IN INDONESIA - Sugandi, Dasep (Journal of Economicate Studies, 2017)
This paper discusses the application of Sharia compliance to industry and Islamic finance business. Sharia compliance is a possible means of preventing risk and fraud in the real sector. This also applies to the innovation of Islamic financial products. Shariah rules are expected to be a guide in the operationalization of Islamic banking in Indonesia. With literature study, this paper found that Shariah compliance serves as an ex-ante (preventive) action and measure, to ensure policies, rules, systems and procedures, and business activities undertaken by Islamic banks. Innovation of Islamic banking products refers to sharia standards and shariah governance sourced from Qur'an and Hadith, guided by international standards, fulfillment of integrity and quality of Islamic banking human resources, suitability of contracts, and not dozens of people as consumers.